Association of HLA‐DQA1 gene polymorphisms with the risk of children primary nephrotic syndrome in Chinese population. Issue 1 (13th July 2018) - Zhu, Bingbing; Zhang, Ruifeng; Yang, Huandan; Yuan, Tingting; Lv, Juan; Peng, Qianqian; Tian, Lijun
Abstract : Background: The association between gene polymorphisms and the risk of primary nephrotic syndrome (PNS) is uncovering recently. This study aims to investigate the relationship between single nucleotide polymorphisms (SNPs) on HLA‐DQA1 gene and the risk of PNS. Methods: In this study, we genotyped eight single nucleotide polymorphisms (SNPs) in the HLA‐DQA1 gene in 501 PNS patients and 532 healthy people in Chinese population. Then we analyzed associations of these SNPs with the clinical features in primary nephrotic syndrome of children in Chinese population. Results: Significant associations with PNS were found on missense SNP rs1129740 (GG vs AA, odds ratio (OR) = 1.987, 95% confidence interval (CI) = 1.468‐2.652, P  = 0.00177049) and rs1047992 (AA vs GG, OR = 1.857, 95% CI = 1.325‐2.391, P  = 1.1073E‐10) of the HLA‐DQA1 gene. Conclusions: This work suggests SNPs of HLA‐DQA1 are risk factors for PNS in Chinese population, which implies roles of immune response in the pathogenesis of PNS.